Impact of Employee Perception Shaped by Despotic Leadership on the Job Performance of Employees: Investigating the Mediating Role of Work Engagement and the Moderating Role of Social Climate of Friendship Groups - Muhammad Saeed Ahmad; Mumtaz Muhammad Khan; Akhtar Mehmood; Usman Ali; Muhammad Navid Iqbal (Journal of Management and Research, 2021)
The effect of employee perception of despotic leadership on employee job performance is an active area of research. The current study used the conservation of resource (COR) theory to investigate the mediating impact of employee work engagement and the moderating role of social climate of friendship groups. For this purpose, a proportionate sampling technique was used. Data was collected from 423 employees of pharmaceutical companies listed on Pakistan Stock Exchange (PSX) by utilizing a dyad approach with predictors (self-reports) and employees’ performance (supervisor-reports). The hypotheses were tested through Hayes Process (2012) and regression analysis. The study results showed that employee perception of despotic leadership is inversely associated with employee job performance and work engagement. Furthermore, this study identified that the impact of this association decreases under the conditions created by the social climate of strong friendship groups. This research explores this broad area and adds to the body of knowledge on dark leadership. The findings of the study have significance for both theory and organizational practice.